Young Investors Interest in Investing in The Capital Market Through Fintech Technology - Johannes Martin Pesireron; Ratih Kusumawardhani; Risal Rinofah (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This study examines the interest of young Yogyakarta student investors in investing in the capital market through fintech technology. Analysis was conducted on the influence of financial literacy, personal interest, and environment on students’ interest in investing. Data was collected through an online questionnaire to 100 Yogyakarta student respondents. The results show that financial literacy has no significant effect on interest in investing, while personal interest and environment have a positive and significant effect. This study contributes to understanding young investors' interest in investing in the capital market through fintech technology. The researcher recommends further research to refine these results.